ANALISIS KEBUTUHAN PELATIHAN TEKNIS DALAM MENINGKATKAN KOMPETENSI PEGAWAI NEGERI SIPIL - Mulyaningsih Mulyaningsih (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
Planning and developing competencies is important to improve Civil Servant performance. Efforts to improve Civil Servant competency carried out through additional training of at least 20 (twenty) hours of study (20 JP) have not been fully accommodated. Training needs analysis has not been carried out effectively. The purpose of this study was to determine the importance of analyzing the need for technical training in improving Civil Servant competencies. The research method used is through a qualitative approach. The results of this study are the analysis of the need for technical training that has not been fully effective in improving Civil Servant competency. This happens because all Civil Servant haven’t the opportunity to develop their competencies through training. In addition, the analysis of technical training needs is still limited to finding data and information of Civil Servant who are interested in participating in the training, not yet carrying out a comprehensive analysis in accordance with the concept.